Politics of Teaching - Richard Ohmann (Radical Teacher, 2022)
[...]college education failed to address or even connect with the deepest concerns of students. According to descriptions of a program called University Studies at Portland State (www.ous.pdx.edu), much of the effort in first year courses goes to establishing small learning communities, each one comprising a faculty member, a peer mentor, and a group of students. [...]post-secondary education comes in ever smaller and precision-marketed units, for customers who are often refashioning themselves to meet the needs of employers. [...]liberal arts enrollments make up a much smaller share in the burgeoning proprietary and public sector, where most of the adult  students seek economic advantage, and business's needs determine what studies will yield that advantage.